Aplicación Móvil Offline multiplataforma para ingreso de datos de ficha familiar del Centro de Salud Chambo usando el framework Flutter. - Chafla Villacrés, Francis Jesús (2025)
In the present research project, a multiplatform offline mobile application was developed using the Flutter framework, in order to evaluate, based on the ISO/IEC 25010 standard, the reliability of transferring family record data from the offline application to the database of the Chambo Type B Health Center, once the application gains internet access. The offline application includes modules for managing facility, family members, pregnancy records, family mortality, and data of the responsible professional. The research type used was quantitative, and the study population was considered infinite, because simulation scenarios were defined with different concurrency levels, to measure reliability in faultlessness, fault tolerance, and recoverability. The tools used in the simulations were JMeter, Jest, and JavaScript scripts, where event and error logs were collected to analyze reliability. For the development of the offline application, the Mobile-D methodology was used, featuring fast and iterative cycles specific to mobile application development. It is concluded the transactions implementation, referential validations, error handling with try-catch blocks, state control for asynchronous synchronization, and logs recording, ensured the data reliability, facilitating the entry Family Record data. The results showed a data recovery capacity over 90% with an MTTR 17 seconds, 100% faultlessness performance in main functionalities, and 100% fault tolerance for partial failures.